Are Your Labor Shares Set in Beijing? The View through the Lens of Global Value Chains - Ariell Reshef; Gianluca Santoni (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the evolution of labor shares in 1995-2014, while taking into account international trade based on value added concepts. Declines in labor shares accelerate in 2001-2007, concurrently with global value chain (GVC) integration, after which there is no trend for both. We develop a gravity-based instrument for GVC integration and find that the acceleration in the decline in labor shares is caused by increased intensity of forward GVC integration. The integration of China into GVCs has a disproportionally large effect through this mechanism. Declines in labor shares are shouldered mostly by less skilled workers in fabrication functions. Relatively capital abundant countries integrate more into forward GVCs linkages, which is associated with greater upstreamness within GVCs and increases in capital intensity. Forward GVC integration is associated with international vertical integration of both upstream intermediate input production and of offshoring of downstream assembly.
Keywords: E25; F14; F15; F16; F66; J00; 330; labor share; global value chains; upstreamness